NEUROPSYCHOLOGICAL AND NEURODEVELOPMENTAL DEFICIENCIES IN PREMATURITY - Narberhaus, Ana; Segarra, Dolors (Anales de Psicología / Annals of Psychology, 2004)
Premature infants show morphological and functional features characterisitic of their immaturity, what make them vulnerable to suffer short or long term complications, being the most frequent of them the hyaline membrane disease, which produces perinatal asphyxia. Perinatal asphyxia can produce intraventricular and periventricular hemorrhages. There are only few studies about the posterior evolution of these subjects. Related to neurodevelopment, premature infants without complications show, in the neonatal period, a cortical grey matter reduction, an increase of lateral ventricles and white matter lesions, more evident when they grow older. At the age of 3-8 years, data essentially show deficits in the intelligence quotient, but at the age of 14-15 studies report deficits in reading and calculation too. On the other hand, premature infants with complications show ventricular dilation, periventricular leukomalacia and atrophy of some subcortical structures. In childhood and at the age of 13 years, these children have difficulties in general cognitive performance and in some specific domains such as memory. In view of this limited data, we suggest an exhaustive neuropsychological and neuroimaging study at long term, to highlight about the consequences of prematurity with or without complications.